How often are ecosystems top‐down controlled? Experiments in grassland, grasshopper, and bird systems over time and space - Gary E. Belovsky; Jennifer B. Slade (Ecosphere, 2024)
Abstract Ecosystems are frequently considered to be controlled by predation (top‐down). Experiments examined this in four bird/spider/grasshopper/prairie habitats over 34 years, employing in each habitat three 100 m2 bird exclosures and controls (121 habitat/year cases) where plant, grasshopper, and spider abundances were measured. Top‐down control (plants decrease and grasshoppers increase with bird exclusion) was observed in only 13.2% of cases, while plants increased and grasshoppers decreased in 33.1% of cases, plants decreased and grasshoppers decreased in 25.6% of cases, and plants increased and grasshoppers increased in 28.1% of cases. Therefore, top‐down control was not common and system responses were not constant, but varied among sites, years, and directionally over time with climate change. This diversity of responses is expected given the variety of underlying processes in complex ecosystems. For example, decision tree/discriminant analysis found that plant decreases and increases with bird exclusion were correctly identified in 78.3% of cases by grasshopper hatchling abundance, plant cover, and annual net primary production (ANPP), while grasshopper decreases and increases with bird exclusion were correctly identified in 76.7% of cases by edible plant biomass per grasshopper hatchling, grasshopper hatchling abundance, and large grasshopper abundance. Analysis of other system‐wide terrestrial trophic experiments indicates that the variety of responses observed by us over time and space may be common so that system‐wide trophic responses may, in general, be more variable than either top‐down or bottom‐up as often considered.